Associations of parent–adolescent closeness with P3 amplitude, frontal theta, and binge drinking among offspring with high risk for alcohol use disorder. (21st January 2023) - Pandey, Gayathri; Kuo, Sally I‐Chun; Horne‐Osipenko, Kristina A.; Pandey, Ashwini K.; Kamarajan, Chella; de Viteri, Stacey Saenz; Kinreich, Sivan; Chorlian, David B.; Kuang, Weipeng; Stephenson, Mallory; Kramer, John; Anokhin, Andrey; et al.
Abstract: Background: Parents impact their offspring's brain development, neurocognitive function, risk, and resilience for alcohol use disorder (AUD) via both genetic and socio‐environmental factors. Individuals with AUD and their unaffected children manifest low parietal P3 amplitude and low frontal theta (FT) power, reflecting heritable neurocognitive deficits associated with AUD. Likewise, children who experience poor parenting tend to have atypical brain development and greater rates of alcohol problems. Conversely, positive parenting can be protective and critical for normative development of self‐regulation, neurocognitive functioning and the neurobiological systems subserving them. Yet, the role of positive parenting in resiliency toward AUD is understudied and its association with neurocognitive functioning and behavioral vulnerability to AUD among high‐risk offspring is less known. Using data from the Collaborative Study on the Genetics of Alcoholism prospective cohort ( N  = 1256, mean age [ SD ] = 19.25 [1.88]), we investigated the associations of closeness with mother and father during adolescence with offspring P3 amplitude, FT power, and binge drinking among high‐risk offspring. Methods: Self‐reported closeness with mother and father between ages 12 and 17 and binge drinking were assessed using the Semi‐Structured Assessment for the Genetics of Alcoholism. P3 amplitude and FT power were assessed in response to target stimuli using a Visual Oddball Task. Results: Multivariate multiple regression analyses showed that closeness with father was associated with larger P3 amplitude ( p  = 0.002) and higher FT power ( p  = 0.01). Closeness with mother was associated with less binge drinking ( p  = 0.003). Among male offspring, closeness with father was associated with larger P3 amplitude, but among female offspring, closeness with mother was associated with less binge drinking. These associations remained statistically significant with father's and mothers' AUD symptoms, socioeconomic status, and offspring impulsivity in the model. Conclusions: Among high‐risk offspring, closeness with parents during adolescence may promote resilience for developing AUD and related neurocognitive deficits albeit with important sex differences. Abstract : High‐risk offspring of individuals with AUD manifest low P3 and frontal theta (FT) reflecting heritable neurocognitive deficits. Conversely, positive‐parenting can be protective and critical for normative development of self‐regulation and neurocognitive functioning. In high‐risk offspring, we examined associations of closeness with parents during adolescence, with offspring P3, FT, and binge‐drinking. Closeness with father was associated with larger P3 and higher FT and closeness with mother was associated with less binge‐drinking. Positive‐parenting may buffer against AUD‐risk and related neurocognitive deficits.